Biodegradation of Doxylamine From Wastewater by a Green Microalga, Scenedesmus obliquus - Xiong, Jiu-Qiang; Cui, Pengfei; Ru, Shaoguo (Frontiers in Microbiology, 2020)
Pharmaceutical contaminants (PCs) have been recognized as emerging contaminants causing unexpected consequences to environment and humans. There is an urgent need for development of efficient technologies to treat these PCs from water. Current study has investigated the removal capacity of a green microalgal species, Scenedesmus obliquus for doxylamine, chemical oxygen demand (COD), and nutrients from real wastewater. Results have indicated that S. obliquus can grow well in the doxylamine-polluted wastewater with achieving 56 %, 78.5 %, 100 %, 89 % of doxylamine, COD, total nitrogen (TN), and total phosphorus (TP). Addition of bicarbonate enhanced the removal of doxylamine up to 63%, and slightly inhibited the removal of COD. Decreased carbohydrate and increased protein content of the harvested biomass have been observed after cultivation in the wastewater. Current study has shown the feasibility of using microalgae-based biotechnologies for PCs-contaminated wastewater.